Peran Tenaga Pendidik dan Orang Tua serta Masyarakat dalam Pendidikan Inklusi (Bimbingan dalam Pendidikan Inklusi) - Nurfadhillah, Septy; Cahyati, Shisy Yulia; Farawansya, Sitti Aisyah; Salsabila, Alya (Lembaga Yasin AlSys, 2022)
This research begins with the basic concept of inclusive education, the role of teachers and parents in inclusive education to the collaboration carried out by parents and teachers in inclusive education. The purpose of this study was to describe the role of teachers and parents, as well as the community in inclusive education at SD Negeri Panunggangan 01. Collaboration between parents and teachers is very much needed in the formation and improvement of inclusive education. Parental involvement is a factor that can encourage and determine the development of inclusive education throughout the world. Parents of children with special needs need to be directly involved in making every decision, starting from school placement to their collaboration with the school. This journal begins with the basic concepts of inclusive education and education, the role of teachers and parents in inclusive education to the collaboration carried out by parents and teachers in inclusive education. The purpose of this journal is for readers to know and understand the importance of the role and collaboration between parents and teachers in inclusive education.